Vasoactivity of the rat endovascular trophoblast. (October 2016) - Ariel, Ilana; Skarzinski, Galina; Belzer, Vitali; Abu Ahmad, Wiessam; Abassi, Zaid; Bursztyn, Michael
Abstract: Introduction: Rat endovascular trophoblasts (EVasT) express smooth muscle (SM) proteins and contract ex vivo upon exposure to endothelin-1 (ET1) via receptors A and B (ETA, ETB). Presently, we investigated the EVasT response to NOS inhibition (N-Nitro-l -arginine methyl ester hydrochloride, l -NAME), and potentiation by NO donor [S-Nitroso-N-Acetyl-D, l -Penicillamine (SNAP)] following KCl precontraction. M&M: Luminal surface area (LSA) of remodeled spiral artery rings (SAR) devoid of SM was measured ex vivo upon exposure tol -NAME alone;l -NAME and ET1 representing the combined contractile effect of both ET1 receptors;l -NAME with ET1 and ETA antagonist, representing the isolated contractile effect via ETB. In another experiment we administered SNAP to KCl precontracted SAR. Statistical analysis was performed using 2-way mixed ANOVA and repeated measures. Results: l -NAME reduced LSA by 2.22%, 95% CI [0.83%, 3.60%] compared with control. ET1 andl -NAME reduced LSA immediately, compared with a plateau at 60min by ET1 alone. The isolated ET1 constrictive effect via ETB, reduced LSA by 5.94%; 95% CI [3.47%, 8.41%], significantly more than that obtained via ETA following 36 min of the experiment by 0.88%; 95%CI [0.09%, 1.67%]. Addition of KCl reduced LSA by 11.9%, 95% CI [9.6%, 14.1%]. Addition of SNAP increased LSA by 3.0%, 95% CI [1.7%, 4.3%]. Conclusions: EVasT of the rat remodeled spiral artery react to ET1 and KCl similar to vascular SM: contract via both ET1 receptors and KCl and relax by ET1 via ETB and by SNAP. This phenomenon may play a role in rat models of gestational vasoactive systems dysregulation. Highlights: EVasT react to ET1 like SM of non-modified arteries: contract via ETA and ETB and relax via ETB through NOS activation. Vascular rings of rat remodeled spiral artery contract ex vivo by blocking constitutive NOS in EVasT. ET1 induces earlier contraction of remodeled spiral artery in the presence of NOS inhibitorl -NAME. Precontracted vascular rings of rat remodeled spiral artery dilate ex vivo following exposure to NO donor SNAP. Potassium chloride (KCl) causes contraction of remodeled spiral artery ring ex vivo similar to non-remodeled arteries.